Nutritional Status and the Risk for Colorectal Adenomas: A Case-Control Study in Hospital Kuala Lumpur, Malaysia - Ramadas, Amutha; Kandiah, Mirnalini (Pakistan Journal of Nutrition, 2010)
The most important and possible risk factor of colorectal adenomas is the individual’s nutritional status. The role of nutritional status in the aetiology of colorectal adenomas remains an area of active investigation, as the exact relationship between nutritional status and colorectal adenomas remains unclear. The objective of this case-control was to determine the nutritional status of subjects with colorectal adenomas as compared with healthy subjects at Hospital Kuala Lumpur over a period of one year. A total of 118 subjects were recruited (n case = 59 and n control = 59). A pre-tested questionnaire was used to collect socio-demographic information and dietary intake. Lipid profile was determined using standard Roche diagnostic kits. The data were analyzed using SPSS version 12.0. The intake of beta-carotene, alpha-carotene, lycopene, vitamin A and crude fiber found to be significantly different between the groups (p<0.05), while beta-carotene, alpha-carotene, lycopene, vitamin C, vitamin D, vitamin E and crude fiber significantly reduced the risk. Although the percentages intake of nutrient achieved according to RNI were below the recommended value, percentages of RNI achieved for vitamin C, D, E and folate were found to be significantly different between male subjects (p<0.05). Our results support the notion that certain nutritional factors are of importance for the development of these pre-cancerous lesions. Identification of risk factors through this case-control study should be able to supplement the available data in order to develop an intervention package that focuses on multiple risk factors to reduce the chances for developing colorectal adenomas or colorectal cancer.